Measuring Failures Proneness: Scale Development and Preliminary Validations - Diamant, Irene; Rusou, Zohar (Frontiers in Psychology, 2021)
Behavioral failures can serve as precursors for accidents. Yet, individual differences in the predisposition to behavioral failures have predominantly been investigated within relatively narrow parameters, with the focus limited to subsets of behaviors or specific domains. A broader perspective might prove useful in illuminating correlations between various forms of accidents. The current research was undertaken as one step toward developing the concept of behavioral failures proneness in its multidimensional aspect. We report the initial stage of the development and validation of the Failures Proneness questionnaire (FP): a brief, multifaceted, self-report scale of common behavioral failures in everyday settings. In a preliminary phase we conceived an extensive pool of prospective items. Study 1 identified and validated the factor-structure of FP and reduced the scale to a brief measure of 16 items. Study 2 corroborated the factor structure of the FP and evaluated its construct validity by assessing its relationship with the Five Factor Model (FFM) of personality traits. Study 3 tested the criterion-related validity of the FP by assessing its ability to predict deviant behaviors. These studies provide evidence of the FP’s performance in generating valuable information on a broad range of behavioral antecedents of accidents.